PEMBUATAN DAN UJI KARAKTERISASI MEMBRAN SERAT BERONGGA POLIETERSULFON UNTUK PROSES PEMURNIAN AIR - Nasrul Arahman (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Polymeric porous membranes are generally prepared by the phase separation of polymer solution. In this work, hollow fiber membrane was prepared by nonsolvent induced phase separation (NIPS). Effect of addition of surfactant Tetronic on the performance and characteristic of resulting membrane were investigated. The control PES membrane has the highest water contact angle, indicating the lowest hydrophilic. With addition of surfactant Tetronic in the polymer blend hollow fiber membrane, the water contact angle decreased indicates that the membrane surface is more hydrophilic. Scanning electron microscopy (SEM) images for all of the membrane showed the structure of fiber with finger-like macrovoids through the cross-section. The sponge-type of structure in the center path of original membrane was disappeared with addition of Tetronic. Ultrafiltration experiment results showed that water permeability was increased with addition of surfactant Tetronic. According to the characteristics of resulting membrane such as hydrophilicity, ultrafiltration performance, and pores structure, surfactant Tetronic was a good additive to produce hydrophilic membrane for drinking water application.